Analgesic effects and distribution of cutaneous sensory blockade of quadratus lumborum block type 2 and posterior transversus abdominis plane block: an observational comparative study - Aoyama, Yuki; Sakura, Shinichi; Abe, Shoko; Wada, Minori; Saito, Yoji (Korean Journal of Anesthesiology, 2020)
Background: The posterior transversus abdominis plane block (TAPB) and quadratus lumborum block (QLB) were developed for postoperative pain control after lower abdominal surgery. However, there is little data regarding their effects. Their analgesic effects and the distribution of the cutaneous sensory blockade were observed in patients undergoing laparoscopic gynecologic surgery. Methods: After an induction of general anesthesia, patients alternately received bilateral ultrasound-guided QLB type 2 (QLB2) or posterior TAPB using 20 ml of 0.375% levobupivacaine on each side. The measurements included visual analogue pain scores (VAS), cutaneous sensory blockade in each dermatome, demands for postoperative analgesics, and complications for up to 48 h after the block. Our primary endpoint was VAS at 24 h after the block. Results: Forty patients completed the study. The VAS at rest was significantly lower after QLB2 than that after TAPB at 48 h, but not at 24 h. Neither group differed in VAS when coughing at any point in time. Postoperative demands for fentanyl and other analgesics also did not differ for either block. The majority of injections produced a cutaneous sensory blockade in the T11 and T12 dermatomes in both groups. The median number of dermatomes blocked was limited to three dermatomes after either block. No severe complication related to either block was observed. Conclusions: The analgesic effects of QLB2 and posterior TAPB did not differ in patients undergoing laparoscopic gynecologic surgery. The cutaneous sensory blockade produced was limited to three dermatomal levels in the majority of patients. However, these findings need to be confirmed through a larger comparative study.